Philippine Agriculture's Institutional Structure of Governance: A Critique - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1997)
To face the challenges and exploit the opportunities created by the agriculture trade liberalization and the devolution of governance, it is important that institutional issues confronting any sector be addressed. It is in this light that this paper aims to analyze the institutional issues affecting the cost and effectiveness of governance of the agriculture, natural resource and environment sectors. What direction institutional reforms should take is proposed.
Keywords: 330; natural resources and environment; governance; agriculture sector; devolution